Histology, fusion status, and outcome in metastatic rhabdomyosarcoma: A report from the Children's Oncology Group. Issue 12 (18th May 2017) - Rudzinski, Erin R.; Anderson, James R.; Chi, Yueh‐Yun; Gastier‐Foster, Julie M.; Astbury, Caroline; Barr, Frederic G.; Skapek, Stephen X.; Hawkins, Douglas S.; Weigel, Brenda J.; Pappo, Alberto; Meyer, William H.; Arnold, Michael A.; et al.
Abstract: Background: Distinguishing alveolar rhabdomyosarcoma (ARMS) from embryonal rhabdomyosarcoma (ERMS) has historically been of prognostic and therapeutic importance. However, classification has been complicated by shifting histologic criteria required for an ARMS diagnosis. Children's Oncology Group (COG) studies after IRS‐IV, which included the height of this diagnostic shift, showed both an increased number of ARMS and an increase in the proportion of fusion‐negative ARMS. Following diagnostic standardization and histologic re‐review of ARMS cases enrolled during this era, analysis of low‐risk (D9602) and intermediate‐risk (D9803) rhabdomyosarcoma (RMS) studies showed that fusion status rather than histology best predicts prognosis for patients with RMS. This analysis remains to be completed for patients with high‐risk RMS. Procedure: We re‐reviewed cases on high‐risk COG studies D9802 and ARST0431 with an enrollment diagnosis of ARMS. We compared the event‐free survival (EFS) and overall survival by histology, PAX‐FOXO1 fusion, and clinical risk factors (Oberlin score) for patients with metastatic RMS using the log‐rank test. Results: Histology re‐review resulted in reclassification as ERMS for 12% of D9802 cases and 5% of ARST0431 cases. Fusion‐negative RMS had a superior EFS to fusion‐positive RMS; however, poorer outcome for metastatic RMS was most related to clinical risk factors including age, primary site, and number of metastatic sites. Conclusions: In contrast to low‐ or intermediate‐risk RMS, in metastatic RMS, clinical risk factors have the most impact on patient outcome. PAX‐FOXO1 fusion is more common in patients with a high Oberlin score, but fusion status is not an independent biomarker of prognosis.